(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Vesicoureteral reflux (VUR), a common pediatric urologic anomaly, predisposes children to recurrent urinary tract infections and renal scarring. Clinical presentation data from resource-limited South Asian settings remain sparse. Objective: To describe the clinical profile of pediatric patients with vesicoureteral reflux at a tertiary care hospital in Bangladesh. Methods: This prospective cohort study was conducted at Bangladesh Medical University, Dhaka, Bangladesh, from January 2024 to December 2025. Eighty-seven children aged <12 years with confirmed VUR on voiding cystourethrography were enrolled using purposive sampling. Data on age, sex, presenting symptoms, history of febrile UTI, and associated anomalies were collected. Data were analyzed using SPSS version 23.0. Results: Of 87 patients, 70.1% were female (median age 18 months). Febrile UTI was the most common presentation (74.7%), followed by antenatal hydronephrosis (20.7%). Bilateral reflux occurred in 56.3%. Among 136 refluxing ureters, grade III VUR was most frequent (36.0%), and moderate-to-high-grade reflux (III–V) accounted for 74.2%. Renal scarring was present in 47.1%, significantly associated with high-grade reflux (p<0.001). Conclusion: Febrile UTI in young females is the dominant presentation of pediatric VUR in Bangladesh. High-grade reflux and renal scarring are alarmingly common, underscoring the urgent need for early diagnosis after febrile UTI in infants and young children. Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 27-31